Too big to die [large type] - Jaffarian, Sue Ann, 1952- (Jaffarian, Sue Ann, 1952- Odelia Grey mystery, 2018)
"It's the dog days of summer for Odelia and Greg after they rescue a dog from a closed car on a blistering hot day. The culprit is former reality star Marla Kingston, who's married to a client of Odelia's law firm. The dog was saved, but Odelia's job might not be when Kingston demands blood. Things get even stickier when a video of the rescue goes viral and the man who helped them winds up dead. And who is the mysterious young woman who shows up about the same time? Is she connected or just an opportunist looking to cash in on their reluctant Internet fame?" --